THE RELATIONSHIP OF THE ROLE OF DRUG SWALLOWING MONITORS (PMO) TO COMPLIANNCE WITH DRUG DRINKING IN PULMONARY TB PATIENTS IN THE KUTA BARO HEALTH CENTER, ACEH BESAR DISTRICT 2023 - Kala, Pasyamei Rembune; najikhah, Nur; Wati, Serlina (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2024)
Tuberculosis (TB) is a chronic, infectious disease that remains a public health problem in the world, including Indonesia. The rate of compliance with taking medication for TB sufferers at the Kuta Baro Community Health Center, Aceh Besar Regency has not yet met the national target. Taking medication for TB sufferers can be done with several combinations of drugs which are intended to eradicate germs. WHO recommends a DOTS treatment strategy, namely that sufferers take medication by supervising drug swallowing monitors (PMO). The aim of this research is to determine the relationship between PMO (Drug Swallowing Monitor) with the presence of taking medication in Tuberculosis patients. The type of research used is analytical descriptive with a cross sectional approach. The results of 11 respondents who were active in the role of monitoring medication swallowing (PMO) and the majority of respondents adhered to taking medication, 9 (64%). Of the 5 who were not active, it was influenced by the role of the PMO.) From the results of the statistical test, P Value = 0.009 means P Value < 0.05, that there is a relationship between the role of supervisor in taking medication and compliance with taking pulmonary tuberculosis medication at the Kuta Baro Community Health Center, Aceh Besar Regency. From the results of the analysis, it was obtained that the OR value = 13,000, that an active PMO role has a 13 times chance of medication adherence compared to an inactive PMO role.